European Court of Human Rights in the Face of Climate Change - Wiśniewski, Adam (PRAWO i WIĘŹ, 2025)
In 2024, the European Court of Human Rights decided three cases related to climate change. He explained the issues regarding the admissibility of complaints in this type of cases. The case of Verein Klimaseniorinnen Schweiz and Others v. Switzerland is of particular importance, as the ECtHR established the link between the rights protected in the Convention and climate change, stating that Article 8, protecting the right to privacy and family life, should be seen as covering the state’s obligation to protect against these changes. It also defined the nature and scope of the state’s positive obligations under the Climate Change Convention. Therefore, the findings of the ECtHR presented in these cases will be of significant importance in similar cases considered in the Strasbourg docket in the future. In the case of Verein Klimaseniorinnen Schweiz and Others v. Switzerland, the ECtHR also established the conditions that must be met in order for an applicant alleging a violation of his Convention rights due to climate change to be considered a victim within the meaning of Art. 34 of the Convention, and these conditions are defined separately for natural persons and for associations that are legal persons. The judgment in the case of Verein Klimaseniorinnen Schweiz and others v. Switzerland can be considered a landmark ruling in terms of threats to human rights resulting from climate change. Having the status of a real precedent, this judgment will certainly encourage further complaints about the negative effects of climate change, which may result in mobilizing national authorities to review national climate policies. Despite the controversy that accompanies it, the ruling in the Verein Klimaseniorinnen Schweiz case may play an important role in mobilizing the authorities of the 46 states parties to the Convention to undertake more intensive efforts to counteract the enormous threats associated with the phenomenon of climate change.